1999
DOI: 10.1046/j.1525-1594.1999.06359.x
|View full text |Cite
|
Sign up to set email alerts
|

Battery‐Powered Implantable Nerve Stimulator for Chronic Activation of Two Skeletal Muscles Using Multichannel Techniques

Abstract: Chronic activation of skeletal muscle is used clinically in representative numbers for diaphragm pacing to restore breathing and for dynamic graciloplasty to achieve fecal continence. The 3 different stimulation techniques currently used for electrophrenic respiration (EPR) all apply high frequency powered implants. It was our goal to make these stimulation methods applicable for EPR by a battery-powered nerve stimulator that would maximize the patient's freedom of movement. Additionally, the system should all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The current implantable device uses a two-coil strategy to protect the weak biological signals from the effects of the strong RF electromagnetic fields generated by the inductive coupling. The impedance reflection technique, utilizing a LSK modulation method, is generally adopted in implantable biomicrosystem applications (Smith et al 1998, Gudnason et al 2001, Lanmüller et al 1999. This study adopts the LSK unit, shown in figure 5, which is modified from the unit described previously by Tang et al (1995).…”
Section: Load-shift Keying (Lsk) Unit For Outward Couplingmentioning
confidence: 99%
“…The current implantable device uses a two-coil strategy to protect the weak biological signals from the effects of the strong RF electromagnetic fields generated by the inductive coupling. The impedance reflection technique, utilizing a LSK modulation method, is generally adopted in implantable biomicrosystem applications (Smith et al 1998, Gudnason et al 2001, Lanmüller et al 1999. This study adopts the LSK unit, shown in figure 5, which is modified from the unit described previously by Tang et al (1995).…”
Section: Load-shift Keying (Lsk) Unit For Outward Couplingmentioning
confidence: 99%
“…Wireless neuromodulation has been a widely researched topic [1][2][3][4] resulting in different practical approaches such as battery-powered [5,6] and remotely operated [7,8] devices, as well as remotely powered and controlled devices. Implants can be remotely powered by ultrasound [7,9], magnetic induction [2,10], radiofrequency electromagnetic waves [11][12][13], as well as driven by light [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…All of the aforementioned methods have the advantage for in vivo experimental and therapeutic usage in comparison to wired devices. However, most of them are attached to a set of limitations and disadvantages, such as a large form factor [24], limited tissue penetration [25] and the need for complex external apparatus for powering and controlling the implants [26]. Implants offering effective and stable operation, minimally invasive form-factor and simple remote power and control would have a distinct advantage over the competing technologies.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are safety and practical constraints on the energy that can be transferred to and/or stored on such devices [1]. As most of this energy is used by the stimulator circuitry, its power efficiency can play a role in prolonging the functional lifetime of a stimulator device (e.g., battery-powered implants [2]), improving the quality of prosthetic function (e.g., more stimulation sites in visual prostheses [3]), or miniaturizing wireless implants (e.g., smaller receiving aperture in mm-sized implants [4], [5]).…”
Section: Introductionmentioning
confidence: 99%